DOMESTIC VIOLENCE - IMPLICATIONS OF THE EUROPEAN COURT OF HUMAN RIGHTS CASE LAW TO THE COURTS PRACTISE IN SERBIA (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
Domestic violence has existed in rudimentary forms of the family, and has persisted until today. It is considered as a manifestation of control and power over family members. Studies have shown that domestic violence leaves grave consequences for the bio-psychosocial condition of the victim, especially if it is a child victim. The European Court of Human Rights was still dealing with this issue, primarily in cases of violation of Article 8, where right to respect for private life stupulated. In addition, the Court dealt with domestic violence, when considering the violation of the right to life, the prohibition of torture, the prohibition of forced labor, the right to a fair trial, the right to an effective legal remedy, and the prohibition of discrimination. Violence in Serbia is a phenomenon, that is, according to statistics, continues to increase. Although in Serbia there is a legal framework for protection against domestic violence, but in the practice of the courts was observed mild penal policy. Inadequate coordination of state authorities in preventing and combating domestic violence, may lead to violation of the positive obligations under the Convention for the country, both in terms of protection of the right to life and the prohibition of torture, inhuman and degradingtreatment. A chronic disease of the judicial system of Serbia, excessive length of judicial proceedings, is directly contrary to the realization of the right to trial within a reasonable time, as well as the effectiveness of the legal remedies. The authors is dealing with relevant cases from the European Court, quoting and noting the conclusions of the judgment, which serve as support to national legislators, in order to create an adequate legal framework for effectiveaction in the case of identifying domestic violence, as well as sanctioning the perpetrators of this crime.